Van Gogh Syndrome - Roka, Y B; Thapa, R; Puri, P R; Aryal, S (Journal of Nepal Health Research Council, 2011)
Self injury is the intentional and direct injury to self that include bite, burn, ulceration and head banging. These injuries are rarely fatal and are usually not suicidal in nature. This behavior is common among adolescents, psychiatric patients and in females. Bipolar disorder, drug abuse and metabolic syndromes like LeschNyhan and Munchausen’s syndrome are often associated with this disorder. Repetitive self mutilation is termed the Van Gogh syndrome after the famous painter who cut off his ear and gave it to a prostitute. We describe two such cases of self mutilation inschizophrenic patients.Keywords: bipolar disorder, psychiatry, self mutilation, Van Gogh syndrome